Radiology of spontaneous biliodigestive fistulas and their complications - Berois, Néstor L (Cirugía del Uruguay, 1972)
Spontaneous biliodigestive fistulas have been found, Uruguay, practical!y by chance. Their detection should be the result of careful studies, placing the patient in diffeernt positions, after having examined him through simple radiography and la ter using contrast: gastroduodenum, colon by enema or ingestion of gaseous liquid, liquid barium sulphate, Hypaque, etc. It is essential that the radiologist be made acquainted with the ·suspected disease and that he be supplied with al! pertinent data. T.V. should be used whenever possible. Should be considered negative cholecystograms, change of position in calculous images, and. neunobilia.